Early Kinetics of Intestinal Infection and Immune Responses to Two Toxoplasma gondii Strains in Pigs - Rahman, Mizanur; Devriendt, Bert; Jennes, Malgorzata; Gisbert Algaba, Ignacio; Dorny, Pierre; Dierick, Katelijne; De Craeye, Stéphane; Cox, Eric (Frontiers in Cellular and Infection Microbiology, 2020)
Toxoplasma gondii is an obligate intracellular parasite, able to infect all homeothermic animals mostly through ingestion of (oo)cysts contaminated food or water. Recently, we observed a T. gondii strain-specific clearance from tissues upon infection in pigs: while the swine-adapted LR strain persisted in porcine tissues, a subsequent infection with the human-isolated Gangji strain cleared parasites from several tissues. We hypothesized that intestinal immune responses shortly after infection might play a role in this strain-specific clearance. To assess this possibility, the parasite load in small intestinal lymph node cells and blood immune cells as well as the IFNγ secretion by these cells were evaluated at 2, 4, 8, 14 and 28 days post oral inoculation of pigs with tissue cysts of both strains. Interestingly, at day 4 post inoculation with the LR strain the parasite was detected by qPCR only in the duodenal lymph node cells, while in the jejunal and ileal lymph node cells and PBMCs the parasite was detected from day 8 post inoculation onwards. Although we observed a similar profile upon inoculation with the Gangji strain, the parasite load in the examined cells was much lower. This was reflected in a significantly higher T. gondii-specific serum IgG response in LR compared to Gangji infected pigs at day 28 post inoculation. Unexpectedly, this was not reflected in the IFNγ secretion upon re-stimulation of the cells where almost equal IFNγ secretion was observed in both groups. In conclusion, our results show that T. gondii first enters the host at the duodenum and then probably disseminates from this site to the other tissues. How the early immune response influences the clearance of parasite from tissues needs further study.